Aspects of western cultural, Intolerance: on the hermeneutical approach to the Mah–abh–arata - Dragonetti, Carmen; Tola, Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
There are frequent manifestations of Western cultural intolerance that prevent a scientific neutral approach to the intellectual achievements of other cultures, and also to appreciate them in their actual value. The authors of this article first refer to examples of this kind of intolerance in the field of Philosophy (which has been the principal object of their last investigations), Religion (Buddhist Atheism), and Linguistics (the «discovery» of Sanskrit language by Western scholars). In the present paper they specifically deal with the hermeneutical approach by Western scholars to the Mah–abh–arata that the authors consider the most important work in World Literature: Intolerance in this matter makes scholars find in the Mah–abh–arata a real «chaos» or conduces them to the obsessive search for the «Ur-Text», giving rise to theories that eliminate large portions of the epic poem considering them interpolations, or negating it all creativity, originality, and even its Indian essence. The last part of the article is dedicated to Krsna, an avatara, i.e. a reincarnation or manifestation, of the Supreme God Visnu. Krsna is seen as «a bizarre figure», «a cynic», «an opportunist», «a charlatan, who declares himself to be the God of Gods». These Western scholars leave completely aside the Indian tradition of almost three thousand centuries that proclaims that Krsna is not a God, but the God of the Hindu people, being adored by many devoted hearts. A simple but important hermeneutical norm has been forgotten: To accept the cultural products created by another culture as they are conceived by it, and without interpreting them according to one’s one cultural criteria based on the own values and beliefs.
Keywords: hermeneutics; cultural intolerance; Philosophy; Religion; Linguistics; Mah–abh–arata; Krsna/Visnu; Avat–ara